AUTHENTIC TEACHING AND ASSESSMENT AS THE SOLUTION TO EDUCATIONAL EVALUATION IN REFERENCE TO ASEAN ECONOMIC COMMUNITY IN INDONESIA - Fadly Azhar (International Journal of Educational Best Practices, 2018)
Abstract: This paper is a monograph of an academic research paper entitled The Implementation of Classroom-Based Assessment within the English Secondary School Teachers in Riau Province-Indonesia (Universiti Kebangsaan Malaysia, 2012). Chronologically, it discloses such aspects as the changes of curriculum, the ignorance of productive skills, the functions of English in ASEAN economic community, the authentic teaching & learning, the authentic teaching materials, the authentic assessment, the related study, and the implications & recommendations.